Arrested Development of Henneguya ictaluri (Cnidaria: Myxobolidae) in ♀ Channel Catfish × ♂ Blue Catfish Hybrids. Issue 2 (3rd June 2019) - Rosser, Thomas G.; Khoo, Lester H.; Wise, David J.; Mischke, Charles C.; Greenway, Terrence E.; Alberson, Neely R.; Reichley, Stephen R.; Woodyard, Ethan T.; Steadman, James; Ware, Cynthia; Pote, Linda M.; Griffin, Matt J.
Abstract: Henneguya ictaluri is the etiologic agent of proliferative gill disease (PGD) in farm‐raised Channel Catfish Ictalurus punctatus and hybrid catfish in the southeastern United States, and significant annual losses are attributed to this disease. Research suggests that H. ictaluri infection dynamics in Blue Catfish I. furcatus and hybrid catfish (Channel Catfish × Blue Catfish) differ from those in Channel Catfish. Two separate infectivity trials were conducted to investigate H. ictaluri development in Channel Catfish, Blue Catfish, and their hybrids. On two separate occasions with two different year‐classes, fish were exposed to pond water containing H. ictaluri actinospores and sampled weekly for 12 weeks (trial 1) or 14 weeks (trial 2). In trial 1, the presence of H. ictaluri was evaluated histologically and by quantitative PCR of fish tissues, including gills, blood, anterior kidney, brain, heart, liver, posterior kidney, spleen, and stomach. Henneguya ictaluri DNA was detected in significantly higher concentrations throughout multiple organ systems in the Channel Catfish compared to the hybrid catfish and Blue Catfish, with the gills having higher quantities. Myxospores were observed in Channel Catfish gill tissue at 8 weeks postexposure. No myxospores were observed in Blue Catfish or hybrid catfish. The second trial focused on gills only and yielded similar results, with Channel Catfish having significantly greater H. ictaluri DNA quantities than hybrids or Blue Catfish across all time points. Myxospores were observed in Channel Catfish beginning at 6 weeks postexposure and were found in 36% (58/162) of Channel Catfish sampled for molecular and histological analysis during weeks 6–14. Myxospores in hybrid catfish were sparse, with single pseudocysts observed in two hybrid catfish (1.2%) at 14 weeks postexposure. These results imply arrested development of H. ictaluri in hybrid catfish. As such, culture of hybrid catfish may be an effective management strategy to minimize the burden of PGD.